DEVELOPMENT OF A LECTORA-BASED ELECTRONIC MODULE FOR DIGITAL SIMULATION SUBJECT IN GRADE X AT SMKN 2 TULUNGAGUNG: A R2D2 MODEL APPROACH - Oktavia Riski Ayu Fatimah; Nurna Listya Purnamasari (JoEICT (Jurnal of Education And ICT), 2025)
The limited availability of digital learning media in vocational secondary schools represents a critical challenge that hampers students' self-directed learning and engagement. This study addresses this gap by developing a Lectora Inspire-based electronic module (e-module) for the Digital Simulation subject in Grade X at SMKN 2 Tulungagung, Indonesia. The development employed the Reflective, Recursive Design and Development (R2D2) model, which encompasses three interconnected phases: Define Focus, Design and Development Focus, and Dissemination Focus. Product validation was conducted through expert review panels comprising a media expert and a subject-matter expert, followed by user trials with student groups. Quantitative data were collected using Likert-scale questionnaires and analyzed using feasibility percentage formulas. Validation results demonstrated that the e-module achieved a media expert feasibility score of 82.8%, a subject-matter expert feasibility score of 92.5%, a small-group trial score of 80.5%, and a large-group trial score of 85.0%. The overall average feasibility index reached 84.75%, classified as "Very Feasible" according to established criteria. These findings confirm that the developed e-module is suitable for deployment as an instructional medium in the Digital Simulation subject, offering a replicable model for technology-enhanced learning material development in vocational education contexts